Factors Influencing High School Students’ Interest in pSTEM - Ito, Tiffany A.; McPherson, Erin (Frontiers in Psychology, 2018)
The transition from high school to college is an important choice point for the pursuit of physical sciences, technology, engineering, and mathematics (pSTEM) career paths as students transition from course selection that is proscribed by state graduation requirements in high school to the potential to choose classes and paths of study more freely in college. Here two studies examine whether social factors identified to inhibit interest in pSTEM within college students similarly affect high school students, and in particular whether these factors could contribute to gender differences in interest in pursuing pSTEM. We find a lower sense of social and ability belonging and lower self-efficacy among female than male high school students pursuing pSTEM classes. In addition, for females but not males, social belonging significantly predicts intentions to continue to pursue pSTEM; thus, low social belonging inhibits intentions to pursue pSTEM for female but not male students. We also find that perceptions of pSTEM fields as requiring innate brilliance more than hard work selectively discourage female students from intending to further pursue pSTEM. Together the studies highlight the impact of both subjective self-perceptions and perceptions about pSTEM fields on students’ interest in pSTEM and further identify processes that may selectively dissuade high school females from pursuing pSTEM career paths relative to males.